Interacting effects of maternal responsiveness, infant regulatory problems and dopamine D4 receptor gene in the development of dysregulation during childhood: A longitudinal analysis - Poustka, Luise; Schmidt, Martin H.; Brandeis, Daniel; Banaschewski, Tobias; Laucht, Manfred (Journal of psychiatric research, 2015)
Recent longitudinal studies have indicated that affective and behavioral dysregulation in childhood is associated with an increased risk for various negative outcomes in later life. However, few studies to date have examined early mechanisms preceding dysregulation during early childhood. Aim of this study was to elucidate early mechanisms relating to dysregulation in later life using data from an epidemiological cohort study on the long-term outcome of early risk factors from birth to adulthood. At age 3 months, mothers and infants were videotaped during a nursing and playing situation. Maternal responsiveness was evaluated by trained raters. Infant regulatory problems were assessed on the basis of a parent interview and direct observation by trained raters. At age 8 and 11 years, 290 children (139 males) were rated on the Child Behavior Checklist (CBCL). Additionally, participants were genotyped for the dopamine D4 receptor (DRD4) exon 3 VNTR polymorphism. A significant three-way interaction between maternal responsiveness, DRD4 genotype and infant regulatory problems was detected predicting the CBCL-dysregulation profile (CBCL-DP). Carriers of the DRD4 7r allele with regulatory problems at age 3 months showed significantly more behavior problems associated with the CBCL-DP during childhood when exposed to less maternal responsiveness. In contrast, no effect of maternal responsiveness was observed in DRD4 7r carriers without infant regulatory problems and in non-carriers of the DRD4 7r allele. This prospective longitudinal study extends earlier findings regarding the association of the CBCL-DP with early parenting and later psychopathology, introducing both DRD4 genotype and infant regulatory problems as important moderators.